Peningkatan Pemahaman Mahasiswa Melalui Sosialisasi Dalam Pencegahan Perilaku Bullying di Kampus Universitas Negeri Padang - Amirah Sakinah; Meliani, Meliani; Alvito Nikola Melindryan; Yulia Hanoselina (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Bullying behavior is an issue that requires serious attention as it negatively impacts the mental health and social development of adolescents. This journal discusses the role of adolescents in creating social awareness about bullying through community empowerment programs. The research used qualitative methods of interviews and focus group discussions to explore the perceptions and experiences of students, teachers, and parents. The results show that adolescents can be effective agents of change in creating a safe and inclusive environment. Programs such as awareness campaigns and leadership training have been shown to increase empathy and understanding for victims of bullying. Research recommendations include collaboration between schools, families, and communities to create an ecosystem that supports bullying prevention.